Aluminum bar cutting optimization for door and window manufacturing - Ageu de Araujo-Machado (Dyna, 2020)
This study aims to optimize the one-dimensional cutting process of aluminum bars for the production of aluminum doors. Reducing the use of bars and the amount of material that becomes scrap is a key factor in process efficiency, reducing the need for raw material procurement. The mathematical model used considers the size of the bar, the number and size of cuts, the size of the leftovers that can be used and the size of the leftovers that are considered scrap. Based on real data from a company in the aluminum frame segment, the mathematical model was used to simulate three different scenarios. Three different objective functions were used in the simulations, and the results obtained in each scenario were described in order to indicate the advantages and disadvantages of using each objective function. For the instance sizes studied, the model is able to obtain optimal solutions with little computational time.